FRI0476 Relative fdg accumulation of the aortic wall lesions to aortic blood pool in 18f-fdg-pet and pet/ct is a useful parameter for assessing the disease activity of takayasu arteritis. (23rd January 2014) - Ihata, A.; Shizukuishi, K.; Kishimoto, D.; Watanabe, T.; Watanabe, R.; Hama, M.; Yoshimi, R.; Ueda, A.; Takeno, M.; Ishigatsubo, Y.
Abstract : Background: There is accumulating evidence that 18 F-fluolodeoxyglucose-positron emission tomography (FDG-PET) and PET/ computed tomography (PET/CT) is useful for monitoring patients with Takayasu arteritis (TA). Objectives: To investigate a quantitative indicator in FDG-PET or PET/CT scans for the disease activity of TA. Methods: We retrospectively investigated 16 TA patients who had FDG-PET or PET/CT scans (total 76 scans) from 2004 to 2012 (all female, 39.1 ± 19.7 years). FDG accumulations in aortic wall lesions of TA was evaluated by semi-quantitative index; the standardized uptake value (SUV). In addition to SUVmax in the aortic wall, we also calculated SUV ratio of maximum aortic wall uptake to mean lung uptake (SUVratio Lu ), SUV ratio of maximum aortic wall uptake to mean liver uptake (SUVratio Li ), and SUV ratio of maximum aortic wall uptake to mean aortic blood pool uptake (SUVratio BP ). We analyzed the relationships of these SUV parameters with the disease activity, which was defined by the level of CRP. We also determined the cutoff levels, sensitivity, and specificity of 4 sets of SUVs (SUVmax, SUVratio Lu, SUVratio Li, and SUVratio BP ) for CRP based disease activity by using Receiver Operating Characteristic (ROC) analysis. Moreover, we compared the correlation of these 4 parameters and CRP. Results: In 76 total PET and PET/CT scan examinations, active (CRP positive) and inactive (negative) groups were 36 and 40, respectively. All 4 sets of SUV in the aortic wall lesions were significant higher in active group than inactive group ( SUVmax : p < 0.001, SUVratio Lu : p < 0.0 5, SUVratio Li : p < 0.0001, SUVratio BP : p < 0.0001 ). ROC analysis revealed that the cutoff point of SUVratio BP was 1.7 resulted in the highest sensitivity of 94.7% and specificity of 81.6% and that the area under the curve was 0.929 (95%CI:0.871-0.929). Among 4 sets of SUVs, SUVratio BP showed the highest coefficient of correlation with the logarithm index of CRP (cor=0.66) . Image/graph: Conclusions: Our data suggest that SUVratio BP, which represents relative FDG accumulation of the aortic wall lesions to aortic blood pool, is the best indicator to assess disease activity of TA. Disclosure of Interest: None Declared